Attentional disengagement from negative natural sounds for high-anxious individuals. Issue 3 (4th May 2019) - Wang, Yanmei; Xiao, Ruiqi; Luo, Cheng; Yang, Libing
ABSTRACT: Background and objectives: Previous studies have not consistently concluded whether high-anxious persons exhibit attentional bias towards negative natural auditory stimuli. The present study explores whether auditory negative stimuli could induce attentional bias to negative sounds in real life and investigates the exact nature of these biases using an emotional spatial cueing task. Design: Experimental study with a mixed factorial design. Method: We created two groups according to the state-trait anxiety scale, namely high and low trait anxiety. Participants ( N  = 68 undergraduate students) were required to respond to an auditory target after receiving a negative (aversive sounds from natural life) or neutral auditory stimuli. Results: A 2 (Validity: valid/invalid)  × 2 (Cue Valence: negative/neutral) × 2 (Anxiety Group: LA/HA) repeated-measures ANOVA on reaction times revealed that participants with high trait anxiety exhibited slower reaction times in invalid trials following negative cues than following neutral cues. Higher levels of trait anxiety were associated with more difficult attentional disengagement from negative auditory information. Conclusions: The results demonstrate that impaired attentional disengagement was one of the mechanisms by which high-anxious participants exhibited auditory attentional bias to natural negative information.